Genotypic variation in transpiration efficiency due to differences in photosynthetic capacity among sugarcane-related clones - Li, Chunjia (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.